2020
DOI: 10.3390/su12083196
|View full text |Cite
|
Sign up to set email alerts
|

Manager’s Age, Sustainable Entrepreneurial Orientation and Sustainable Performance: A Conceptual Outlook

Abstract: Scholars have investigated the direct linkage between manager's age and sustainable corporate performance, however, the mixed results and conflicting findings on the nature of the relationship demand further explanation through the missing constructs. Therefore, the purpose of this paper is to examine the mediating role of sustainable entrepreneurial orientation in the manager's age and sustainable performance. This study develops a conceptual link by using a dynamic capabilities approach and upper echelon per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 75 publications
(129 reference statements)
0
14
0
2
Order By: Relevance
“…In the present study, we focused on non-psychological factors, namely, age, education and experience that influence sustainable and project performance in small and medium enterprise (SMEs). The existing literature has paid attention to these factors and have scrutinized the positive relationship between managerial demographic factors and organizational outcomes (Ameer and Khan, 2020; Nadkarni and Herrmann, 2010). However, so far, studies have not emphasized on these factors in sustainability management and project performance of SMEs operating in emerging economies.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we focused on non-psychological factors, namely, age, education and experience that influence sustainable and project performance in small and medium enterprise (SMEs). The existing literature has paid attention to these factors and have scrutinized the positive relationship between managerial demographic factors and organizational outcomes (Ameer and Khan, 2020; Nadkarni and Herrmann, 2010). However, so far, studies have not emphasized on these factors in sustainability management and project performance of SMEs operating in emerging economies.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The success of a project depends on the project manager's ability to ensure a timely response, efficient use of resources, a caring environment and adhering to budget constraints (Schmid and Adams, 2008). A recent study conducted by Ameer and Khan (2020) that managers' age significantly affects sustainable business performance. Müller and Turner (2007) revealed that project managers' age and nationality influence project success.…”
Section: Literature Review and Building Hypothesesmentioning
confidence: 99%
“…Finally, age plays a complex relationship with entrepreneurship given the several contextual factors that may influence youth entrepreneurial motivations and actions (Esson, 2015), especially in the agricultural sector (Bezu and Holden, 2014;Brixiov a et al, 2015). On the one hand, age and experience might hamper EO when farmers or other firm managers have developed immutable mental schemas (Ameer and Khan, 2020) or little motivation for change (Siren et al, 2017). On the other hand, age and experience might relate with more knowledge and ability to take "calculated risks", therefore supporting EO .…”
Section: Institutional and Demographic Antecedents Of Entrepreneurial Orientationmentioning
confidence: 99%
“…From the perspective of measuring entrepreneurship education, entrepreneurial performance is one of the key impact indicators. This evaluation indicator can provide a more detailed evaluation of entrepreneurial innovation capabilities and the effectiveness of entrepreneurship education (Ameer and Khan, 2020). In the evaluation and selection of innovation and entrepreneurship, the psychological factors of individual participants will inevitably have an impact on the entrepreneurial process and results.…”
Section: Introductionmentioning
confidence: 99%